Konsep Penciptaan Alam Semesta Dalam Al-Qur’an dan Sains - Ramadhan Syah Nasution (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The universe and all its regularities become an important object of study in both religious and scientific perspectives. In the classical view, as proposed by Isaac Newton, the universe is considered static without beginning and end. However, the development of science, such as the Friedman Model and the Big Bang theory, shows that the universe is dynamic and has a creation process. This study aims to analyze the concept of the creation of the universe in the Qur'an and science with a complementary approach. The Qur'an describes the creation of nature in six periods, as found in QS. An-Nazi'at: 27-33, which indicates the stages of creation from nothingness to the formation of the earth and the sky. Meanwhile, science explains the origin of the universe through the Big Bang theory, which states that the universe emerged from a huge explosion about 13.8 billion years ago. This study also compares the views of figures such as Hamka and Quraish Shihab, who harmonize the concept of creation in the Qur'an with scientific findings, although there is debate regarding God's role in the process. By exploring Qur'anic verses and their interpretation in the context of science, this research seeks to create a constructive dialog between religious and scientific perspectives on the origin of the universe.